A Case Study of the Personal Experiences on Instructional Leadership of Middle-Level Leaders during Pandemic - Llave, Catherine; Genon, Cynthia (JPAIR Institutional Research, 2022)
The pandemic has brought disruption in the educational setting. This sudden disorder has to be handled properly and quickly by the management, specifically the middle managers, to ensure a smooth delivery of learning and teaching. Holding on to the assumption that middle managers have a special function during a crisis, this study explored the instructional leadership of middle managers during the pandemic in a private institution using the Philippine Professional Standards for Supervisors. Using qualitative phenomenological design and employing focus group discussion as a data gathering technique to inquire on the middle managers’ handling of the academic condition, results reveal that implementation of the curriculum was smoothly done even if they are not well-equipped with the current situation. This study clearly emphasized that middle managers’ critical function, especially in turbulent times, for the smooth delivery of instructions by monitoring the teachers’ well-being professionally and emotionally and providing needed academic assistance. Hence, we recommend that academic institutions enhance the managerial aspect of middle managers by including disaster and risk mitigation. It is also recommended to look after the welfare of the middle managers. The key role they play is crucial to sustaining the delivery of academic excellence.